Patient satisfaction with Indonesian sharia hospital services: Halal healthcare tool and implications for loyalty-WoM - Alfarizi, Muhammad; Arifian, Rafialdo (Asian Journal of Islamic Management (AJIM), 2023)
Purpose − Analyze the psychology of patients related to halal healthcare tools that impact their loyalty intentions to Sharia hospitals in Indonesia for health visits and the implications of word of mouth on the community.Methodology − The research employed quantitative techniques by utilizing cross-sectional survey information gathered from Sharia hospital patients in Indonesia, selected through convenience sampling methods. The study analyzed a total of 229 patient responses through the application of structural equation modeling.Findings − Sharia facilities, doctor-nurse services, medical expertise and administrative conduct as indicators of halal health services affect patient satisfaction in sharia hospitals. However, there is resistance to the influence of the medical facility atmosphere on satisfaction caused by the concentration of patients in medical services and solving health problems. Patient satisfaction affects loyalty which in turn gives a positive word of mouth effect.Implications − Islamic hospitals should prioritize patient assessment and satisfaction by reviewing their physical facilities, cleanliness, comfort, and spiritual needs. Medical personnel should enhance communication and sharia-compliant practices. Digitalization and improved service standards are essential, requiring adaptability and technology integration. Regular evaluations and external monitoring are vital. The government should collaborate with relevant ministries and organizations to intensively monitor and improve the quality of sharia hospitals. Originality − This study develops new knowledge on indicators of special services for sharia hospitals according to halal standards by integrating the outputs of satisfaction, loyalty and Word of Mouth (WoM) outputs which have been separated so far but have a chronological sequence in line with existing marketing theory.